Implikasi Hukum Daluwarsa Utang Pajak bagi Wajib Pajak dan Negara - Pandini, Anindya Intan; Putri, Merliani Riskiana; Patmawati, Nanda (Judge : Jurnal Hukum, 2025)
Tax debt is an amount of tax that must still be paid by the Taxpayer to the state and is part of the state's right to be collected in accordance with applicable laws and regulations. In some conditions, tax debt can end due to payment, compensation, exemption, deletion, or expiration. Of the five methods, expiration is an important issue because it concerns the aspect of legal certainty and the temporal limitations of the state's right to collect taxes. This study aims to find out how the legal regulations related to the expiration of tax debt in Indonesia are and what are the legal implications of the expiration of tax debt for taxpayers and the state. The research method we use is a data collection method, namely a normative legal study carried out by collecting various data. In the context of tax debt, expiration means that after a certain period of time, the state loses the right to collect taxes from the party in debt. Through the third amendment to the KUP Law with Law Number 28 of 2007, the expiration period for tax collection which was previously 10 years was shortened again to 5 years. For taxpayers, the expiration of tax debt has a legal impact that is freeing from financial responsibility for tax obligations that have passed the collection deadline. From the perspective of the state, the expiration of tax debt can have a serious impact on the loss of the right to collect state revenue that has been legally determined. Therefore, the expiration of tax debt should not be seen as a legal weakness, but rather as a control mechanism that tests the effectiveness of the state's tax administration function.